THE QUALITY COMPARSION OF SVD AND DCT BASED IMAGE COMPERSSION METHODS FOR EMBEDDED DEVICES (Perner's Contacts, 2011)
This article presents results of the SVD based asymmetric image compression method for static image data in comparison to conventional compression methods based on DCT. The described method has been developed as an additional method for transferring static images transfer to personal video portable units from a central control system.
Keywords: Lossy image compression; SVD; DCT; Image processing; Embedded devices